2019
DOI: 10.4314/ahs.v19i2.21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hepatitis C viremia status on lung functions in chronic hepatitis c patients

Abstract: BackgroundPrevious trials have investigated the effect of hepatitis C on lung functions; however, the role of viral load levels is unclear. The aim of this study was to investigate the effect of HCV viremia status on lung functions.MethodsThis study was in 60 patients with chronic hepatitis C (CHC). Patients were classified into three groups (non-viremic, low-viremic and high-viremic) based on serum HCV RNA levels. Spirometric parameters (FEV1, FVC, FEV1/FVC) and the proportion of patients with spirometric abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Results were in line with the previous study. [15] Similarly, the study by Mahmoud M. El-Habashy et al found that patients with COPD who also had chronic HCV infection had significantly lower lung function than those who did not have HCV. These results imply that persistent HCV infection contributes to the rapid decrease of pulmonary function seen in COPD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Results were in line with the previous study. [15] Similarly, the study by Mahmoud M. El-Habashy et al found that patients with COPD who also had chronic HCV infection had significantly lower lung function than those who did not have HCV. These results imply that persistent HCV infection contributes to the rapid decrease of pulmonary function seen in COPD patients.…”
Section: Discussionmentioning
confidence: 94%
“…The other finding here was the association between chronic hepatitis C infection and fetal pulmonary neuroendocrine cells, which has not been reported in any study so far. Bal et al, reported that patients having high doses of serum chronic hepatitis C RNA levels were 14.2 times more likely to show pulmonary dysfunction than non-viremic patients [ 57 ]. Segna and Dufour also reviewed the association between the hepatitis C virus (HCV) and endocrine and pulmonary manifestations [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…These sometimes affects lung function, which leads to secondary effects with symptoms of progressive liver disease and drug treatment for HCV. Also, the presence of viremia is associated with a spirometric abnormality due to inflammation of the lungs (23). China is reported to have a varying prevalence of HCV infection compared to the neighboring countries (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…sure of oxygen with that of carbon dioxide. According to the findings, patients with a positive HCV RNA had raised liver function tests compared to those with a negative anti-HCV antibody test (23). Subclinical HCV infection increases the risk of deterioration of liver functions.…”
Section: (36)mentioning
confidence: 98%